Enhancing perioperative planning: three-dimensional printing templating in orthopaedic surgery - Domy Pradana Putra; Edi Mustamsir; Krisna Yuarno Phatama; Ananto Satya Pradana; Felix Cendikiawan (Medicinski glasnik, 2025)
Aim: 3D printing technology revolutionises orthopaedic surgery by creating accurate patient-specific models, surgical guides, and implants. The COVID-19 pandemic accelerated this trend, allowing localized solutions and biocompatible materials to replicate bone geometric complexity, enabling surgeons to plan and rehearse surgeries. This study aims to illustrate the use of 3D printing in the preoperative planning of a complex distal femur fracture. Methods: A 42-year-old woman with a complicated Gustilo-Anderson grade III-A fracture underwent 3D printing for implant planning, contouring, and screw trajectory visualization. The procedure took seven hours, and the surgery lasted only two hours, with no complications or complaints during a one-month follow-up. Results: 3D printing has revolutionized orthopaedic surgery by better visualizing complex fractures, reducing surgical time, and enhancing precision. Traditional 2D imaging techniques struggle to capture intricate details, requiring 3D printing for accurate preoperative planning and implant selection. However, challenges include high costs, time, and specialized training. Further research is needed to understand long-term outcomes. Conclusion: The benefits of 3D printing in orthopaedic surgery, including improved visualization, reduced time, and improved precision, highlight its potential for further advancement.
Keywords: 3D printing; advance care planning; distal femur fracture; high-cost; technology